Endometriosis and its impact on female sexuality (Research, Society and Development, 2024)
Introduction: Endometriosis is a chronic, benign, estrogen-dependent gynecological condition that affects women's quality of life, with symptoms such as chronic pelvic pain and infertility. Dyspareunia, in particular, influences female sexual function, affecting desire and sexual response. Objective: This study seeks to understand the impact of endometriosis on the sexuality of women with the condition and how it affects their quality of life. Methodology: This is an narrative literature review conducted through research in the databases BVS, SciELO, PubMed, and scientific journals between 2019 and 2023. Results: Endometriosis is a condition that affects women's physical and mental health and may be associated with malignant ovarian tumors, such as endometrioid adenocarcinoma and clear cell carcinoma. Endometriosis impacts various aspects of women's lives, such as sexuality, work, and overall quality of life. Studies show that it directly influences female sexual function, affecting relationships and self-esteem. Healthcare professionals need to be aware of these impacts to provide comprehensive care and improve the quality of life of patients. Conclusion: Therefore, it is evident that endometriosis affects the quality of life of women. Further studies are needed to improve early diagnosis and ensure access to effective treatments.